ORGANIZATION OF TEACHER TRAINING TO FACILITATIVE INTERACTION WITH STUDENTS - І.М. Avdeeva; N.L. Byezhanova (Academy of Cognitive and Natural Sciences, 2022)
The article introduces the pedagogical education organization model according to the psychological regularities of the personality's standing mental new features formations.